Diplomacy of the Emirate of Bukhara during the Time of Amir Heydar - Kurbanmurat , Turayeva is the daughter of Charos (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2024)
In this article, the history of diplomacy, foreign policy, embassy relations, development of trade, including friendship with Russia, mutual cooperation and development of economic and social spheres of the Bukhara Emirate during the reign of Amir Haydar are analyzed with the help of scientific.